Plant Dispersal in a Temperate Stream by Fish Species With Contrasting Feeding Habits: The Role of Plant Traits, Fish Diet, Season, and Propagule Availability - Boedeltje, Ger; Klutman, Bert; Schaap, Michiel; Sollman, Philip; de Vos, Matthijs; Lenssen, John P. M.; Verberk, Wilco C. E. P. (Frontiers in Ecology and Evolution, 2019)
Whether fish mediate plant dispersal in temperate freshwaters is largely unknown. A prerequisite for successful dispersal is ingestion and surviving the journey in the intestinal tract. This study asks whether plant propagules are being ingested under field conditions and what factors shape dispersal potential, focusing on differences across plant species and propagule form (seed or fragment), seasonal differences and plant and fish traits that facilitate dispersal. We focused on three common fish species reported to differ in foraging strategy. Fish were caught monthly over a one-year period in a Dutch lowland stream. Before they were returned to the stream, fish were kept in water for 26 h and their faeces were collected, resulting in 150 faecal samples. Excreted animal remains and plant propagules were identified and enumerated. Plant propagules were tested for viability. In total, 88,579 vegetative fragments of vascular plants, 316 of mosses and 14 of charophytes were identified. Viability was low (<<1%) except for mosses (53.5%). Roach (Rutilis rutilis) and Rudd (Scardinius erythrophthalmus) displayed a preference for filamentous algae and certain plant species (i.e. Elodea nuttallii and Lemna sp.), likely because they were more palatable. Of the 1787 generative propagules of vascular plants that were identified, 120 germinated (6.7%), representing 15 species. Betula pendula, Juncus effusus and Poa trivialis were most abundant. Tench (Tinca tinca) egested most seeds, despite being the least herbivorous species. Particularly, germination was high for seeds that were light (<1.07 mg) and that floated for a long time. Our results show that fish do ingest plant propagules under field conditions and that fish can contribute to vegetative dispersal of vascular plants and several aquatic and riparian moss species. Ingestion of propagules is affected by water temperature and season, their availability in the propagule bank, and their palatability. Both seed traits (related to buoyancy, size and hardness) and fish traits (related to size and identity) were important. Despite substantial dietary overlap, the three fish species displayed subtle differences in their diet, and together can act as vectors for the dispersal of a range of plant and moss species of freshwater systems.